THE IMPACT OF OPERATING ENVIRONMENT FACTORS ON REITS’ DEVELOPMENT AND PERFORMANCE IN NIGERIA - Olanrele, Olusegun Olaopin; Said, Rosli; Daud, Md Nasir; Ab Majid, Rohayu (Journal of Surveying, Construction and Property, 2018)
In spite of the decades’ long global acceptance and adoption of the real estate investment trusts (REITs) as a rewarding investment vehicle with dual advantage of liquidity and market stabilisation for real estate, the pace of REIT adoption and development in the Africa continent is low. Perhaps, the growth and performance of African REITs in term of number of firms, capitalisation and return have made Africa REIT not to feature in Global REIT reports. This paper assess the performance of Nigeria REIT (N-REIT) and the influence of the operating environment on N-REIT The study adopted risk adjusted return analysis based on index computation of REITs weekly trading report for the period July 2010 to May 2014 with Nigerian Stock Market All Share Index (ASI) as benchmark. A questionnaire survey was employed for the effect of operating environment on N-REIT performance. The study found that N-REIT underperforms the ASI. The Informal factors of political risk, infrastructure and security risk are contributing factors to low performance and by extension less developed REIT market in Africa. The study recommends transparency in political leadership and African market, infrastructure development and social security for the growth of the REIT regime in the continent.